Oxidatively stable curcumin‐loaded oleogels structured by β‐sitosterol and lecithin: physical characteristics and release behaviour in vitro. (23rd May 2019) - Li, Linlin; Wan, Wenbo; Cheng, Weiwei; Liu, Guoqin; Han, Lipeng
Summary: In this study, oleogel structured by β‐sitosterol and lecithin was prepared as a carrier for poorly water‐soluble bioactive compounds, curcumin. The mechanical and microscopic properties of curcumin‐loaded oleogel were determined by texture analyser and polarised light microscopy. The oxidation stability of the delivery system was determined by accelerated oxidation test and the bioaccessibility of curcumin was studied in vitro . The results showed that the existence of curcumin did not affect the mechanical strength and crystalline network of oleogel. The oxidative stability of curcumin‐loaded oleogel was higher than that of curcumin‐free oleogel and corn oil‐curcumin mixtures. It might be attributed to not only the antioxidative property of curcumin but also crystalline network of oleogel which served as an obstructor for the development of oxidation products. Additionally, oleogel enhanced the bioaccessibility of curcumin in fasted state (up to 67.66%). These findings suggest that oleogels can be promising candidates to delivery drugs and nutrients. Abstract : Oleogel structured by β‐sitosterol and lecithin was prepared as carrier to deliver curcumin. The interaction between 3‐dimensional network of oleogel and curcumin was demonstrated by evaluating oxidation stability of delivery system and in vitro bioaccessibility of curcumin.